Preparing social workers in Poland as a historical and pedagogical problem - Шевченко, Ж. М. (Scientific notes of the pedagogical department, 2019)
In the context of modern educational challenges, the expediency of taking into account the requirements for the practical training of specialists for social work in the context of continental integration, mobility in the European labor market and the need to take into account the leading trends in the development of social education abroad, as well as the introduction of innovative approaches in the process of training future social workers in Ukraine.Improving the practical training of specialists for the social sphere of Ukraine, where the system of training specialists is at the stage of its formation, may become the experience of neighboring Poland, which is today much more extensive and meets the demands of the modern labor market in developed European countries. The identification of progressive ideas of the practical experience of vocational training of social workers in Poland will contribute to the scientific substantiation of the strategy for the development of professional training of specialists in the social sphere in Ukraine at the stage of its transformation and integration into the European and world educational space.The article actualized the necessity of a historical and pedagogical study on the problem of practical training of social workers in Poland in order to creatively introduce a positive Polish experience for higher education in Ukraine. The article analyzes the state of research of the problem of practical training of social workers in the Polish higher education institution in scientific sources. The analysis of psychological and pedagogical literature has shown that programs of professional training of future social specialists in Ukraine and abroad contain a practical component, which includes not only acquaintance of students with methods and methods of work, but also direct involvement of them in practical activity under the guidance of experienced teacher educators and lecturer-consultants.The current state of the practice of training social workers is the need to diversify the priorities of vocational training of social workers with its further development as a holistic system, the expansion of the spectrum of specializations on the basis of taking into account the achievements of world practice. The necessity of historical and pedagogical research on the identified problem is determined and prospects of further exploration in this direction are outlined.